PENGARUH LINGKUNGAN KERJA, MOTIVASI DAN KOMPETENSI TERHADAP KINERJA PEGAWAI KANTOR PERTANAHAN KABUPATEN PONOROGO - Woody Jauhari Rosyid; Nugroho Mardi W; C. Sri Hartati (Journal of Applied Management and Accounting Science, 2021)
This study aims to describe the work environment, motivation, competence and performance of employees in the Ponorogo Regency Land Office. To analyze the influence of the work environment on employee performance. To analyze the influence of motivation on employee performance. To analyze the influence of competence on employee performance. The population in this study were all employees in the Land Office of Ponorogo Regency as many as 93 people. A sample of 93 people with a sampling technique using a type of non-probability sampling, namely total sampling (census). Data collection techniques using questionnaires and documentation. The data analysis technique used is multiple linear regression. The results obtained from this study are the work environment is in a fairly good category, work motivation, competence and employee performance are in good categories. The work environment has a significant effect on employee performance in the Ponorogo Regency Land Office. Work motivation does not have a significant effect on employee performance in the Ponorogo Regency Land Office. Competence has a significant effect on employee performance in the Ponorogo Regency Land Office.